2011
DOI: 10.1155/2011/584652
|View full text |Cite
|
Sign up to set email alerts
|

Silent Uterine Rupture with the Use of Misoprostol for Second Trimester Termination of Pregnancy : A Case Report

Abstract: Uterine rupture is an uncommon, but a life-threatening, complication following second trimester medical termination of pregnancy (TOP). The reported cases have been in both the scarred and unscarred uterus (Rajesh et al. 2002, Drey et al. 2006, and Dickinson). A 27-year-old with two previous deliveries, no previous caesarean section, no history of induced abortions, and no gynaecological operations. She presented with amenorrhoea, and according to her last normal menstruation, she was 10 weeks and 5 days. Ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…However, some studies have demonstrated that it may result in higher rates of tachysystole, hyperstimulation, meconium passage, uterine rupture and cesarean delivery rate compared to traditional methods [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have demonstrated that it may result in higher rates of tachysystole, hyperstimulation, meconium passage, uterine rupture and cesarean delivery rate compared to traditional methods [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Güleç et al recommended that misoprostol should be used carefully at patients with one or more prior cesarean sections (5). Also, in literature there are many case reports about uterine rupture at patients with prior surgery after using misoprostol (6,7,8) In our study, the patient had prior surgery; a myomectomy and a cesarean section concomitantly and uterine rupture was occurred with low dose misoprostol. In conclusion, misoprostol have to be used carefully at patients with prior uterine surgery.…”
Section: Discussionmentioning
confidence: 67%
“…They suggested that this uterine rupture resulted from an unrecognized perforation in a previous intrauterine manipulation. Many cases have been reported of uterine rupture in an unscarred uterus during second trimester pregnancy termination with intravaginal misoprostol [23]. Chang et al reported a case of a multiparous who had a previous vaginal birth delivery and who was labor-induced with PGE2 and oxytocin.…”
Section: Uterine Rupture In An Unscarred Uterusmentioning
confidence: 99%